Customer Loyalty on Internet Protocol Television (IPTV) in Thailand - Chalita Srinuan; Pratompong Srinuan (International Telecommunications Society (ITS), 2015)
This study aims to investigate the customer loyalty on Internet Protocol Television (IPTV) in Thailand. Data were collected from the accidental sampling which consists of 400 IPTV customers in Bangkok through the self-administered questionnaire in 2014. Descriptive statistics, including percentage, mean and standard deviation, path analysis were employed for hypothesis testing. The results showed that majority of respondent are female, age between 18-25 years old, work at private company and have average income 10,000-20,000 THB. Customer expectation and customer loyalty have a highest impact to customer loyalty if compared to others variables. Service providers should attempt to enhance the content, improve the user interface, system reliability and connectivity as customer will regard the service as valuable service. This could help service providers maintain and gain their market share, increasing their profitability and performance.
Keywords: 330; IPTV; Customer loyalty; Thailand